Evaluation of Food and Nutrition Security Level at Provincial Level Based on Outcome Indicators in Indonesia - Vidyarini, Andra; Martianto, Drajat; Syarief, Hidayat (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2021)
This study aims at evaluating the situation of Food and Nutrition Security (FNS) at provincial level using six outcome indicators. The cross-sectional study, utilized secondary data from 33 provinces published in 2013. It used a modification of the Global Hunger Index (GHI) method and changed the number of outcome indicators. In addition, an equalization was performed, so that the results obtained were positive. The results showed that all provinces in Indonesia have moderate or less secure food and nutrition level. Hence, the performance of the Indonesian government in food and nutrition security need to be improved. Bali Province had the highest rank in food and nutrition security, while East Nusa Tenggara and Papua Province had the lowest ranks of the 33 provinces during 2013. The low performance achievement of food and nutrition security based on the six outcome indicators signified by the high prevalence of the undernourished population and the high prevalence of stunting and wasting of children under five in all provinces in Indonesia.